Na putiakh radikal'noi reformy: perestroika ekonomiki . Na putiakh radikal'noi reformy: perestroika ekonomiki . On the Ways of Radical Reform: Economic Reform . На путях радикальной реформы: перестройка экономики - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. A new law on the democratization of group activities (enters into force on 1 January 1988) includes the formation of profit-distribution mechanisms, self-government, elections, etc. Featured in the program: Stroganov, Genrikh Borisovich (Deputy Chairman of the State Planning Commission) Contributors: Voznesenskii, Lev Aleksandrovich (Anchor) Вступление в силу нового закона (с января следующего года), предусматривающего демократизацию работы коллективов: формирование механизмов распределения прибыли, самоуправление, проведение выборов, и т.д. В программе участвуют: Строганов, Генрих Борисович (Заместитель председателя Госплана) Создатели: Вознесенский, Лев Александрович (Ведущий/Ведущая)